PENGARUH LITERASI KEUANGAN TERHADAP MANAJEMEN KEUANGAN PRIBADI PADA MAHASISWA KONSENTRASI MANAJEMEN KEUANGAN SYARIAH (ANALISIS PENGGUNAAN SHOPEEPAY PADA APLIKASI SHOPEE) - Rachmat Sugeng; Muliana Muliana; Ifa Annisa (ITB AAS INDONESIA Surakarta, 2023)
The improvement of digital technology influences several industries, including the financial industry. One of the most popular technology-based financial services is digital payments. Personal financial management is influenced by several factors, one of them is financial literacy. The purpose of this study was to specify the effect of financial literacy on personal financial management in students of Islamic financial management concentration in the function of shopeepay on the shopee application. This research is a quantitative research using a non-probability sampling method. This study allocated questionnaires to 50 respondents and then processed them statistically using IBM SPSS 26 and simple linear regression methods. The results of this study indilmply that financial literacy has a positive effect on the personal financial management of students who concentrate on islamic financial management in the use of shopeepay on the shopee application.